Application of Metagenomic Next-Generation Sequencing in HIV-Infected Patients with Bloodstream Infections - Liu H; Xu T; Fu H; Dai B; Xie Y (Infection and Drug Resistance)
Huiting Liu, Tianzhen Xu, Hongxin Fu, Bohao Dai, Yirui Xie State Key Laboratory for Diagnosis and Treatment of Infectious Diseases, National Clinical Research Center for Infectious Diseases, Collaborative Innovation Center for Diagnosis and Treatment of Infectious Diseases, The Department of Infectious Diseases, The First Affiliated Hospital, School of Medicine, Zhejiang University, Hangzhou, 310003, People’s Republic of ChinaCorrespondence: Yirui Xie, State Key Laboratory for Diagnosis and Treatment of Infectious Diseases, National Clinical Research Center for Infectious Diseases, Collaborative Innovation Center for Diagnosis and Treatment of Infectious Diseases, The Department of Infectious Diseases, The First Affiliated Hospital, School of Medicine, Zhejiang University, Hangzhou, 310003, People’s Republic of China, Tel/Fax +86-571-87236416, Email 1312019@zju.edu.cnBackground: Bloodstream infections (BSI) are common complications in HIV-infected patients and are prone to septic shock and death. This study aimed to analyze the application of blood metagenomic next-generation sequencing (mNGS) in HIV-infected patients with BSI.Methods: Fifty-four HIV-infected patients with suspected BSI were hospitalized at the First Affiliated Hospital of the Zhejiang University School of Medicine between August 2020 and June 2023. Blood mNGS and blood culture (BC) results were retrospectively reviewed and compared to the application value of BSI.Results: The mNGS was more sensitive for detecting pathogens (82.4% versus 35.3%; P < 0.05), and when combining blood mNGS with culture results, the sensitivity increased to 88.2%. The detection rate of mNGS for blood-mixed infection was significantly higher than that of BC (P < 0.05). Among the positive results for fungi and bacteria detected by mNGS, 13.5% of the pathogenic microorganisms were consistent with the results of BC.Conclusion: The mNGS combined with BC can improve pathogen detection sensitivity and the comprehensive identification of pathogenic microorganisms in HIV-infected patients with BSI.Keywords: metagenomic next-generation sequencing, blood culture, bloodstream infections, HIV